Needs Analysis for Collaborative and Experiential Civic Education in Higher Education - Nurdiansyah, Edwin; Sapriya; Darmawan, Cecep; Aim Abdulkarim; Aulia Novemy Dhita (Journal of Pedagogy and Education Science, 2025)
Civic Education in higher education is expected to develop reflective, critical, and socially responsible citizens. However, its implementation often remains conventional and less connected to real-life civic experiences. This study aims to describe the current state of Civic Education learning at the university level and identify the need for transformation toward a more collaborative and experiential model. Employing a qualitative descriptive approach, data were collected through non-participatory classroom observations in eight Civic Education classes at Universitas Sriwijaya, supported by lecturer and student questionnaires. Thematic analysis revealed four major issues: limited collaboration with external stakeholders, lecture-dominated teaching methods, minimal use of contextual learning resources, and assignments that lack participatory engagement. These findings highlight a gap between the ideal vision of Civic Education and its practical application. The study underscores the urgency of redesigning Civic Education to emphasize student collaboration, contextual relevance, and experiential learning. It recommends developing innovative learning models that align Civic Education with 21st-century civic challenges and learner needs.